To all the skins I’ve bought before: The influence of consumer-centric fear of missing out (FoMO) and its antecedents on the consumption of nonfunctional virtual items in free-to-play video game environments - Montalbo, Gillian Maegan Rosales (Animo Repository, 2023)
With the far-reaching expansion of social media, FoMO, or the “fear of missing out,” has risen to be a pervasive social phenomenon in modern pop culture. This study extends the FoMO literature by examining the complex set of relationships that exist between the individual-level antecedents of consumer-centric FoMO (i.e., consumer independence and consumer need for uniqueness), its underlying dimensions (i.e., desire for belonging and anxiety of isolation), and its consequences on players’ conformity and conspicuous consumption of non-functional virtual items in free-to-play games. The data were collected from 400 respondents through homogeneous purposive sampling. To analyze the research constructs, the researchers performed confirmatory factor analysis, structural equation modeling, and mediation analysis. The findings revealed that consumer need for uniqueness positively affects FoMO. In contrast with theoretical predictions, gamers’ anxiety of isolation has a positive association with the consumption consequences of FoMO due to the unique social interaction environment of free-to-play games. The researchers also found that consumer-centric FoMO fully mediated the relationship between gamers’ need for uniqueness and their conformity and conspicuous consumption of non-functional items. The operable implications of the findings were also discussed.